Effect Of Feed Additives On In Vitro Fermentation Kinetics And Substrate Utilization With And Without Buffer (Applied Biological Research, 2017)
The study was aimed to evaluate the effect of various categories of feed  additives on rumen fermentation. Fermentation kinetics and substrate  utilization by rumen microbes was studied by fortifying the substrate  having roughage to concentrate of 60:40 with glucogenic viz., glycerol and  propylene glycol (PG), rumen fermentation modifiers viz., para  aminobenzoic acid (PABA), exogenous fibrolytic enzymes (EFE) and  probiotic feed additives by applying first order kinetics model to in vitro gas production (IVGP) technique. Glycerol was more effective than PG for  substrate fermentation kinetics and its utilization, particularly IVTVFA  production. Buffer addition was more effective with PG but not with  glycerol. PABA had non-significant impact on either substrate  fermentation kinetics or utilization. EFE fortification significantly  improved the extent of fermentation, IVNDFD and IVTVFA; however,  probiotics showed only significant increase in IVDMD (P
Keywords: Buffer; enzyme; glycerol; PABA; probiotics; propylene glycol; fermentation kinetics